2016
DOI: 10.1159/000445032
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic Transparenchymal Nodule Access: Feasibility and Safety in an Endoscopic Unit

Abstract: Background: The minimal invasive investigation of solitary pulmonary nodules becomes increasingly important with the emergence of lung cancer screening. Objectives: We report the results of the first utilization of a recently developed procedure in a bronchoscopy suite, which approaches solitary pulmonary nodules via a transparenchymal path. Methods: This study was a prospective, single-arm interventional study. We investigated patients with a solitary pulmonary nodule detected on CT imaging, which was suspici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…Complication rates of 38.8% for core biopsies and 24% for FNA from radiologists performing CT‐guided percutaneous lung biopsy were reported in a recent meta‐analysis . Another new approach to diagnosing these lesions includes bronchoscopic transparenchymal biopsies, in which pilot studies have shown to have a diagnostic yield of 83%, although with a higher pneumothorax rate (up to 33%) . A combined procedural approach for the diagnosis of pulmonary nodules by attempting a bronchoscopic diagnosis first to limit complications, followed by a percutaneous biopsy if the bronchoscopy is non‐diagnostic, may be effective in limiting overall complications and increasing diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates of 38.8% for core biopsies and 24% for FNA from radiologists performing CT‐guided percutaneous lung biopsy were reported in a recent meta‐analysis . Another new approach to diagnosing these lesions includes bronchoscopic transparenchymal biopsies, in which pilot studies have shown to have a diagnostic yield of 83%, although with a higher pneumothorax rate (up to 33%) . A combined procedural approach for the diagnosis of pulmonary nodules by attempting a bronchoscopic diagnosis first to limit complications, followed by a percutaneous biopsy if the bronchoscopy is non‐diagnostic, may be effective in limiting overall complications and increasing diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%
“…If the lesion is extrabronchial, we suggest switching to other means of airway exploration that enable taking deeper biopsies, including PPLs located on the outside of the airway wall. Currently used candidate approaches include rEBUS [17, 23] (which allows insertion of larger forceps through the guide-sheath than can be inserted through the working channel of the UTB), VBN-guided fine-needle aspiration [24] (which can obtain blind cytobiopsies after an extrabronchial lesion is located with the VBN system), or transparenchymal nodule access [25, 26] (which could also be used for approaching lesions when segmentation is suboptimal since a straight path could be taken from the end of the segmented airway to the PPL). Although mini-cryobiopsy probes are not commercially available yet, it is thought that they can potentially obtain tissue surrounding distal bronchi [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another small safety and feasibility study showed a 100% concordance rate between biopsies obtained by BTPNA and final pathology results in resected specimens. 43 However, a pneumothorax was identified in two out of the six patients, one of whom required chest tube insertion. The tunnel length did not correlate with pneumothorax risk.…”
Section: Bronchoscopic Transparenchymal Nodule Accessmentioning
confidence: 92%